Model Pembelajaran SAVI (Somatic, Auditory, Visualization, Intelectual) Untuk Meningkatkan Kemampuan Membaca Puisi: Sebuah Inovasi Pembelajaran Bahasa Indonesia di SD - Nini Ibrahim (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The goal in this study to determine how high the SAVI learning model can improve students' ability to read poetry.The research method is a Class Action Research (PTK / Classroom Action Research) using Class Action Research model of Stephen Kemmis and Robin Mc.Taggart.Research results illustrated that, in the first cycle is used SAVI learning model to improve the ability to read poetry. In the first cycle, only 11 (eleven) children who have managed in accordance with the expectations of ≥70%. After some reflection based on studies first cycle, then drafted a plan of action on the second cycle. Action on the second cycle is equal to the action on the first cycle that uses the SAVI learning model. In the second cycle, can be obtained from the data that all students experience a corresponding increase in minimum completeness criteria (KKM), namely achieving good success ≥79.3%. From the results of data analysis cycle I to cycle II, an increase of 14.6%.The conclusions of this research is the ability to read poetry fifth grade students of SDN Tugu X increased by using the SAVI learning model.